RETRACTED: Developing Artificial Intelligence (AI)-Based Children’s Storybooks through Fry Readability for Elementary Students: The Editor-in-Chief has retracted this article because it has been previously published - Nurul Istiq'faroh; Maryam Isnaini Damayanti; Hendratno Hendratno; Asri Susetyo Rukmi; Arie Widya Murni; Amiruddin Hadi Wibowo; Azka Faridy (Scientia Publica Media, 2025)
Education in Indonesia shapes children’s character, personality, and abilities, but faces challenges like unequal access to resources, quality differences between regions, and low reading interest among children. This study aims to develop AI-based children’s storybooks through the Fry readability for elementary students. This study used the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Results showed that AI-based storybooks can improve children’s reading interest and help teachers provide support based on students’ competence. The score of Expert validation was 37 out of 40 (92.5%), and media expert validation was 52 out of 55 (94.5%). Fry readability ensures the reading level is suitable for fourth to sixth-grade students to improve the quality of elementary education in Indonesia, reduce regional quality gaps, and improve students’ academic performance. The AI-based storybooks significantly boost children’s interest in reading, address low reading engagement, assist teachers in offering more effective educational support, and help bridge educational quality gaps between different regions. The alignment with children’s cognitive development ensures engaging and developmentally appropriate content, demonstrating an innovative approach to educational tools and paving the way for further technological integration in education. Therefore, the development of AI-based children’s storybooks with the Fry readability approach not only increases children’s reading interest but also assists teachers in providing more specific support according to students’ abilities. This innovation is expected to positively impact the quality of elementary education in Indonesia, help address educational quality disparities between regions, and enhance students’ academic achievements at the national level.